The impact of outpatient acute kidney injury on mortality and chronic kidney disease: a retrospective cohort study. Issue 3 (22nd March 2018) - Leither, Maxwell D; Murphy, Daniel P; Bicknese, Luke; Reule, Scott; Vock, David M; Ishani, Areef; Foley, Robert N; Drawz, Paul E
Abstract: Background: Acute kidney injury (AKI) has been extensively studied in hospital settings. Limited data exist regarding outcomes for patients with outpatient AKI who are not subsequently admitted. We investigated whether outpatient AKI, defined by a 50% increase in creatinine (Cr), is associated with increased mortality and renal events. Methods: In this retrospective study, outpatient serum Cr values from adults receiving primary care at a health system during an 18-month exposure period were used to categorize patients into one of five groups (no outpatient AKI, outpatient AKI with recovery, outpatient AKI without recovery, outpatient AKI without repeat Cr and no Cr). Principal outcomes of all-cause mortality and renal events (50% decline in estimated glomerular filtration rate to <30 mL/min/1.73 m 2 ) were examined using Cox proportional hazards models. Results: Among 384 869 eligible patients, 51% had at least one Cr measured during the exposure period. Outpatient AKI occurred in 1.4% of patients while hospital AKI occurred in only 0.3% of patients. The average follow-up was 5.3 years. Outpatient AKI was associated with an increased risk of all-cause mortality {adjusted hazard ratio [aHR] 1.90 [95% confidence interval (CI) 1.76–2.06]} and results were consistent across all AKI groups. Outpatient AKI was also associated with an increased risk of renal events [aHR 1.33 (95% CI 1.11–1.59)], even among those who recovered. Conclusions: Outpatient AKI is more prevalent than inpatient AKI and is a risk factor for all-cause mortality and renal events, even among those who recover kidney function. Further research is necessary to determine risk factors and identify strategies for preventing outpatient AKI.